'The Practical is Political' — Duncan Forrester and the 'Political Service' of Theology in Scotland. Issue 3 (3rd July 2017) - Gay, Doug
Abstract : This review article offers a critical historical review of the development of Practical Theology in Scotland over the past 40 years, drawing on original research into the work and influence of internationally renowned scholar, Duncan Forrester, including interviews with Duncan. It contributes significant new analysis of how Duncan's work, developed in the particular historical context of the rise of Thatcherism, radically transformed previous understandings of the scope of the practical theological domain. This contribution has not been fully researched to date and was influential not only in Scotland but internationally, due to the reach and influence of Duncan's work and of his successors in the New College Chair, Will Storrar and Oliver O'Donovan. The article draws on this analysis to offer new perspectives on how disciplinary identities and hierarchies develop and change within theology and argues that practical theology must continually redefine its obligations for contextual engagement.